The role of discursive opportunity in contesting public issues: the struggle over food security discourse - Farley, Isla (2019)
Organisations wield extraordinary power in contemporary society. Much of this power is exercised through the strategic use of language as a variety of actors and organisations compete with each other, and with governmental authorities, to influence the political system (Hoffman & Ford 2010). The discursive struggles that take place around contested issues such as modern slavery, climate change and global food security can be conceived of as public issue framing contests (Dahan & Gittens 2010; Ryan 1991). The extent to which organisations are able to engage effectively with discursive opportunities presented by the socio-political context affects the level of influence they have on the outcomes of such contests (Koopmans & Statham 1999). Consequently, some are able to play a much more prominent role than others in shaping public discourse and influencing how shared global challenges are responded to, including what resources get deployed, where, and by whom (Boin et al 2008). This thesis takes a critical perspective on discourse in organisations in order to explore how issues of power and political agency affect the relative capacity of different organisations to engage with discursive opportunities to influence the outcomes of public issue framing contests.